Ecological transcriptomics – a non‐lethal sampling approach for endangered fire salamanders. Issue 12 (30th July 2015) - Czypionka, Till; Krugman, Tamar; Altmüller, Janine; Blaustein, Leon; Steinfartz, Sebastian; Templeton, Alan R.; Nolte, Arne W.
Summary: The analysis of transcriptomes is well‐established and increasingly affordable in studies at the interface of ecology and evolution. Expression analysis of thousands of genes in parallel reveals functions and pathways involved in relevant phenotypic differentiation. The application of such methods typically involves the sacrifice of the analysed organisms, which is potentially subject to ethical and legal constraints. As an alternative to lethal sampling, transcriptome analyses can be performed using small biopsies of dispensable tissues. It has to be verified, however, to what extent such results are representative of the whole organism. Here, we use a custom microarray to compare transcriptomes of tail‐clip samples with those of the remaining whole body of fire salamander larvae ( Salamandra salamandra ). The microarray was calibrated using target RNA to validate the performance of each probe. We varied water temperature to test whether the thermal response in gene expression can be characterized in both types of sample. A large fraction (51%) of the differentially expressed genes showed parallel changes for both tail clips and whole bodies in response to temperature. While sets of differentially expressed were not identical, they largely belonged to the same functional categories. The gene functions thus revealed a common thermal response of larvae irrespective of the sampled tissue. This included an overexpression of mitochondrial transcripts, an expected thermal acclimatization response of ectotherms. Hence, ecological transcriptomics based on small biopsies represent an alternative to the analysis of lethally sampled tissues in situations where the sacrifice of individuals is not an option.